A Trajectory Planning Model for the Manipulation of Particles in Microfluidics - Meacci, Luca; Rocha, Franciane Fracalossi; Silva, Arianne Alves; Pramiu, Petterson Vinicius; Buscaglia, Gustavo Carlos (Trends in Computational and Applied Mathematics, 2018)
Many important microfluid applications require the control and transport of particles immersed in a fluid. We propose a model for automatically planning good trajectories from an arbitrary point to a target in the presence of obstacles. It can be used for the manipulation of particles using actuators of mechanical or electrical type. We present the mathematical formulation of the model and a numerical method based on the optimization of travel time through the Bellman’s principle. The implementation is focused on square grids such as those built from pixelated images. Numerical simulations show that the trajectory tree produced by the algorithm successfully avoids obstacles and stagnant regions of the fluid domain.